Efeito da adição de suco clarificado de caju nas caractéristicas tecnólogicas e propriedades sensoriais da kombucha - Freitas, Ana Karoline Nogueira (2022)
The kombucha is a fermented beverage made from tea from the leaves of Camellia sinensis, sugar and symbiotic culture of bacteria and yeasts (SCOBY). It can have the addition of other raw materials that act as partial or total substitutes for traditional ones changing its chemical composition and sensory characteristics. Thus, the present work was intended to verify the effects of addition of clarified cashew apple juice (cajuína) in the process, in the chemical composition and sensory properties of kombucha. Three treatments were elaborated with the addition of cajuína: T2 (30% cajuína added in the first fermentation), T3 (30% cajuína added with kombucha acidity close to 3 g of acetic acid/L) and T4 (30% cajuína added at the end of fermentation); and T1 (Kombucha without the addition of cajuína). The physicochemical parameters, color, sugars, polyphenols, flavonoids and antioxidant activity were analyzed before and after the fermentation process. The sensory analysis of the finished beverages consisted of the evaluation of acceptability, sensory characterization and preference ordering of the treatments. The addition of cajuína did not prevent the fermentation of traditional kombucha, with changes in the L*, a* and b* values as its addition was delayed in the kombucha. There was a difference (p<0.05) in the consumption of sugars between the kombuchas produced, with T2 presenting the lowest amount of residual sugars after fermentation. The polyphenols content of the treatments increased with the addition of cajuína compared to the T1 treatment, but the final polyphenol content was lower than the initial one and T4 showed the highest value, 111,06 mg GAE/100 mL. The final flavonoid concentrations were 20,15 mg QE/mL (T1), 19,11 mg QE/mL (T2), 25,74 mg QE/mL (T3) and 15,26 mg QE/mL (T4). There was no significant difference (p>0.05) in antioxidant activity showing values between 9647,00 uM Trolox/L and 13041,61 uM Trolox/L at the end of fermentation. All the kombuchas produced had values between 5 and 7 for appearance and aroma, differing in the attributes taste, overall acceptance and purchase intention with T4 having the best acceptance in these attributes. Of the 27 terms listed in the test Check All That Apply (CATA), five showed a significant difference (p<0.05) by the Cochran’s Q test. For the Rate All That Apply (RATA) test, 14 terms showed a difference with their intensities varying from very little to very much between the treatments. The addition of cajuína made it possible to obtain new beverages with increased sensory acceptability as the inclusion of cajuína in kombucha processing was delayed.